(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Brazilian Rainforest is the habitat of many species of the genus Brachycephalus, among them is the pumpkin toadlet, Brachycephalus ephippium. X-ray microcomputed tomography is a nondestructive imaging technique which allows the visualization and analysis of internal microstructures of various samples, and has been applied on the study of these animals, enabling thorough description and characterization of new species. Brachycephalus ephippium is of particular interest for it was the first Brachycephalus species to be discovered, which makes it a common interspecies comparative basis. Cranial morphological landmarks used in biological research are very small (0.1-1mm), hence the effects of voxel size on microCT images can be relevant, and this is what was investigated in this work. Effects of reconstruction voxel size were evaluated in both visual and quantitative perspectives, which showed that an intermediary voxel size could be chosen on similar microCT applications without significant loss of information, but with great processing and storage gain, optimizing the application of the technique in such works.